1973
DOI: 10.1038/bjc.1973.58
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Malignant Cell Invasion in vitro by a Proteinase Inhibitor

Abstract: Summary.-The inhibitory effect of the protease inhibitor aprotinin (Trasylol) on the invasion of mouse kidney explants by polyoma virus transformed BHK21 cells was investigated using a mixed cell/organ culture technique. The extent of invasion was monitored by following the changes in LDH isoenzyme pattern in the explants and by histological assessment. The kidney explants containing aprotinin were found to maintain a normal kidney LDH pattern and to suffer considerably less invasion than the explants not cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0
1

Year Published

1974
1974
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 12 publications
1
21
0
1
Order By: Relevance
“…In relation to malignant cells, it has been suggested that, by the destruction of the normal surrounding tissue, proteolytic enzymes play a part in tumour cell nutrition as well as in invasion and metastasis (Poole, 1973;Latner et al, 1973a). However, the finding of cellular necrosis accompanied by marked round cell infiltration in both a sarcoma and a carcinoma treated by aprotinin has led us to believe that in some way the proteolytic enzymes of malignant cells may prevent immunological surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to malignant cells, it has been suggested that, by the destruction of the normal surrounding tissue, proteolytic enzymes play a part in tumour cell nutrition as well as in invasion and metastasis (Poole, 1973;Latner et al, 1973a). However, the finding of cellular necrosis accompanied by marked round cell infiltration in both a sarcoma and a carcinoma treated by aprotinin has led us to believe that in some way the proteolytic enzymes of malignant cells may prevent immunological surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, it has been demonstrated that cancer cells can release proteolytic enzymes (Holmberg, 1961;Taylor, Levy and Simpson, 1970), and that proteases can induce proliferation in confluent cell cultures (Burger, 1970;Sefton and Rubin, 1970). On the other hand, protease inhibitors have been shown in vitro to restore contact inhibition of movement (Goetz, XVeinstein and Roberts, 1972) and also to inhibit malignant invasion (Latner, Longstaff and Pradhan, 1973a). Although recently it was found that soybean trypsin inhibitor can reduce the number of recoverable Ehrlich ascites tumour cells from mice by up to 920% (W;hur, Robson and Payne, 1973), no study of the solid tumour controlling capabilities of a proteinase inhibitor in vivo has been reported.…”
mentioning
confidence: 99%
“…PROTEASE inhibitors have been shown to inhibit tumour growth (Latner et al, 1974;Verloes et al, 1978) and invasiveness (Latner et al, 1973) in animal model systems. In addition, other recent evidence (Latner & Turner, 1976;Burden et al, 1978) has suggested that these substances may be operating in cancer by stimulating the host's immunological response.…”
mentioning
confidence: 99%
“…Of the wide range of naturally-occurring and synthetic protease inhibitors currently available, some, including aprotinin, impair the growth of malignant cells and their non-malignant homologues in vitro (Coetz et al, 1972;Latner et al, 1973;Roblin et al, 1975). Thus, although the original claim of Schnebli and Burger (1972) that the growth-inhibitory effects of protease inhibitors are directed selectively against malignant tumour cells, has not beeni suibstantiated (Hynes, 1 976;Schuiebli, 1975) nevertheless, inhibition of maligniant cell growth by protease inhibitors lends to the view (Bosmann and Hall; Easty and Easty, 1976; Hynes, 1976;Schnebli, 1975;Sylven, 1967) that tumour cell proteases potentiate the growth of malignant tumours.…”
mentioning
confidence: 99%
“…Thus, although the original claim of Schnebli and Burger (1972) that the growth-inhibitory effects of protease inhibitors are directed selectively against malignant tumour cells, has not beeni suibstantiated (Hynes, 1 976;Schuiebli, 1975) nevertheless, inhibition of maligniant cell growth by protease inhibitors lends to the view (Bosmann and Hall; Easty and Easty, 1976; Hynes, 1976;Schnebli, 1975;Sylven, 1967) that tumour cell proteases potentiate the growth of malignant tumours. However, evaluation of aprotinin as an anti-tumour agent in vivo by various authors has produced variable results (Back et al, 1966;Back and Steger, 1976;Cliffton and Agostino, 1964;Giraldi et al, 1977;Latner et al, 1974;Thomson et al, 1977).…”
mentioning
confidence: 99%